The in situ near-total pancreatectomy (LIVOCADO procedure) for end-staged chronic pancreatitis - Baron, Ryan D.; Sheel, Andrea R. G.; Farooq, Ammad; Kleeff, Jörg H.; Contin, Pietro; Halloran, Christopher M.; Neoptolemos, John P. (Langenbeck's archives of surgery, 2021)
Beger operation; Extra-hepatic portal hypertension; Frey operation; Pain; Surgery; Varices